2005
DOI: 10.1002/app.21459
|View full text |Cite
|
Sign up to set email alerts
|

Flow marks in injection molding of polypropylene and ethylene–propylene elastomer blends: Analysis of morphology and rheology

Abstract: This paper reports an investigation of asynchronous flow marks on the surface of injection molded parts and short shots made from two different blends of polypropylene and ethylene-propylene random copolymer elastomers. Flow marks were observed on the surface with both blends; the spatial frequency of flow marks on the surface was greater in the blend B1, which also exhibited a greater contrast between the surface regions. The same blend was distinctly faster in the linear viscoelastic tests of shear creep rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…The dispersed phase was highly stretched to cylindrical strands in the glossy surface regions and retracted in the dull regions to some extent. This phenomenon was observed by Patham et al [76] in the injectionmolded blends of PP and EPR (ethylene-propylene random copolymer ) elastomers. Furthermore, the concentration of the dispersed phase in the flow mark region might be different from the out-of-flow mark region.…”
Section: Morphology Of the Surface Defect Called Flow Markssupporting
confidence: 61%
See 1 more Smart Citation
“…The dispersed phase was highly stretched to cylindrical strands in the glossy surface regions and retracted in the dull regions to some extent. This phenomenon was observed by Patham et al [76] in the injectionmolded blends of PP and EPR (ethylene-propylene random copolymer ) elastomers. Furthermore, the concentration of the dispersed phase in the flow mark region might be different from the out-of-flow mark region.…”
Section: Morphology Of the Surface Defect Called Flow Markssupporting
confidence: 61%
“…They attributed this to the preferential phase segregation mechanisms during injection molding as well as the surface energy difference between polymer components [69,70,77], The polymer component with low surface energy tended to segregate at the surface due to low polymer-air surface tension [78]. However, the result obtained by Patham et al [76] was not in agreement with the results mentioned above: the same concentration of the dispersed phase existed in both regions.…”
Section: Morphology Of the Surface Defect Called Flow Marksmentioning
confidence: 98%
“…Brodil and Sehanodish, 12 examining thermoplastic polyolefins (TPO), showed that the rubber particles were elongated in the glossy region and were contracted in the dull ones. A similar observation was also reported by Patham et al 11 A corresponding difference in molecular orientation is also expected for a neat polymer. In Ref.…”
Section: Final Remarks and Conclusionsupporting
confidence: 72%
“…A fast relaxation of this stress difference would reduce the severity of the defects. However, as noted by Patham et al, 11 the relaxation characteristics must be carefully monitored. They observed that a too fast retardation of the elongated ethylene-propylene rubber particles in a PP-matrix, actually could enhance the difference in rubber deformation between the glossy and the dull regions, thus enhancing the flow marks.…”
Section: Final Remarks and Conclusionmentioning
confidence: 98%
“…Some models for the induction distance of the stripe have been proposed in previous studies 12, 14, 15. The authors note that the contact force of the molten blends to the mold wall is an important factor in estimating the induction mechanism.…”
Section: Resultsmentioning
confidence: 99%